Catatonia in adult anti-NMDAR encephalitis: an observational cohort study - Huiting Wu; Chunmei Wu; Yingying Zhou; Shanshan Huang; Suiqiang Zhu (BMC Psychiatry, 2023)
Abstract Background Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is one of the most prevalent autoimmune encephalitis and is closely related to catatonia. This study aimed to investigate the clinical features and disease outcomes of adult catatonic anti-NMDAR encephalitis patients. Methods Adult patients diagnosed with anti-NMDAR encephalitis between January 2013 and October 2021 were retrospectively enrolled in this study. According to the Bush Francis Catatonia screening instrument (BFCSI), patients were divided into two groups: those with catatonia and those without catatonia. The modified Rankin scale (mRS), Clinical Assessment Scale for Autoimmune Encephalitis (CASE), Neuropsychiatric Inventory (NPI), Patient Health Questionnaire-9 (PHQ-9) and 7-item Generalized Anxiety Disorder Questionnaire (GAD-7) scores were assessed at follow-up. The Mann–Whitney U test (nonparametric), Student’s t test (parametric), and chi-squared test were used to analyse the differences between the two groups. Results Eighty-four patients were recruited, including twenty-five catatonic patients and fifty-nine noncatatonic patients. Among them, 28 had positive antibody only in cerebrospinal fluid (CSF), 4 had positive antibody only in serum and 52 had positive antibody both in CSF and serum. Catatonic patients experienced more disturbance of consciousness (p = 0.01), aggression (p = 0.046) and affective disorders (p = 0.043) than noncatatonic patients. The mRS scores of the catatonia group assessed at admission (p = 0.045) were worse than those of the non-catatonia group. Catatonic patients were more inclined to develop deep vein thrombosis (p = 0.003), decubitus (p = 0.046), pneumonia (p = 0.025), and to be admitted to the intensive care unit (ICU) (p = 0.011) than noncatatonic patients. All patients in the catatonia group received first-line immunotherapy. At the 24-month follow-up, 2 patients in the catatonia group did not achieve good outcomes. At the last follow-up, the catatonia group had more relapses (p = 0.014) and more neuropsychiatric problems (p = 0.035). Conclusions Adult anti-NMDAR encephalitis patients with catatonia present distinct clinical features in disease course and are prone to experience more relapses and long-term neuropsychiatric problems than those without catatonia.